Recensement d'éléphants dans la Réserve Communautaire du Lac Télé, République du Congo - Fortuné Iyenguet; Guy-Aimé Malanda; Bola Madzoke; Hugo Rainey; Catherine Schloeder; Michael Jacobs (Pachyderm)
"We surveyed elephants in the 4400-km2 Lac Télé Community Reserve in the Republic of Congo to provide estimates of population status and trends. Habitat in the reserve consists of seasonally flooded and swamp forest with patches of terra firma forest. Using line transects and distance sampling techniques we estimated elephant densities from dung counts in both low- and high-water seasons (flooding seasons). We estimated that the reserve holds low densities of elephants in seasonally flooded and swamp forest. Elephants are present in the terra firma forest in the high-water season only. Our estimate in 2004 of 316 (95% CI 98, 1045) elephants in the reserve is similar to that found in 2002. However, there was a large error in calculating estimates because of the low number of dung piles. Further surveys may help to reduce this error and provide information on elephant distribution between habitats."